EFFECT OF PINK PIGMENTED FACULTATIVE METHYLOTROPH AND PLANT GROWTH REGULATORS ON GROWTH, CHLOROPHYLL, TRANSPIRATION, SOD ACTIVITY AND YIELD OF TOMATO UNDER DROUGHT - R. SIVAKUMAR; P. CHANDRASEKARAN (The Bioscan, 2021)
An experiment was carried out to find out the effect of Pink Pigmented Facultative Methylotroph and Plant Growth Regulators on alleviating the drought effects in tomato. Pot culture experiment was conducted in tomato variety PKM 1 and foliar spray of PGRs like brassinolide (1 ppm), salicylic acid (100 ppm), benzyl amino purine (100 ppm), gibberellic acid (10 ppm) and PPFM (1%), PPFM (2%), and PPFM (3%) were carried out under drought condition. Among the PGRs and different concentrations of PPFM used, PPFM (2%) was found to superior in improving root length (25.90 cm), transpiration rate (32.12 mmol H 2 O m-2 s -1 ) and SOD activity (358.45 Units mg / protein) under drought. The higher plant height of 78.66 cm was registered by GA3 followed by 2% PPFM (75.33 cm). Foliar spray of BAP (100 ppm) maintained higher total chlorophyll content of 2.31 mg g -1 followed by 2% PPFM (2.15) and brassinolide (1.82) under drought. Among the treatments, foliar spray of PPFM (2%) registered highest fruit yield of 477.9 g plant -1 . Hence, PPFM (2%) is used to mitigate the drought effect efficiently and improving the drought tolerance capacity of tomato crop.